2010
DOI: 10.1007/s12012-010-9092-9
|View full text |Cite|
|
Sign up to set email alerts
|

A Combination of Melatonin and Alpha Lipoic Acid has Greater Cardioprotective Effect than Either of them Singly Against Cadmium-Induced Oxidative Damage

Abstract: Present study evaluates cardioprotective role of melatonin (Mel), alpha lipoic acid (ALA), a combination of melatonin and alpha lipoic acid (Mel + ALA) against cadmium (Cd)-induced oxidative damage. Female albino rats were subjected to 15-day exposure to Cd (5.12 mg/kg bw) alone or treated with ML (10 mg/kg bw) + ALA (25 mg/kg bw) simultaneously. Plasma markers of cardiac damage, cardiac free radical generation, lipid peroxidation, endogenous antioxidant status, cadmium load, metallothionein induction, and his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 67 publications
2
24
1
1
Order By: Relevance
“…A combination of melatonin and alpha‐lipoic acid has a greater cardio‐protective effect than either of them alone against cadmium‐induced oxidative damage . Melatonin also benefits rat cardiac mitochondria and the survival rate after septic myocardial injury . Furthermore, melatonin protects against isoproterenol‐induced alterations in cardiac mitochondrial energy‐metabolizing enzymes and apoptotic proteins and assists in complete recovery from myocardial injury in rats .…”
Section: Discussionmentioning
confidence: 99%
“…A combination of melatonin and alpha‐lipoic acid has a greater cardio‐protective effect than either of them alone against cadmium‐induced oxidative damage . Melatonin also benefits rat cardiac mitochondria and the survival rate after septic myocardial injury . Furthermore, melatonin protects against isoproterenol‐induced alterations in cardiac mitochondrial energy‐metabolizing enzymes and apoptotic proteins and assists in complete recovery from myocardial injury in rats .…”
Section: Discussionmentioning
confidence: 99%
“…The same study and additional investigations in our laboratory , Genade et al 2008) and elsewhere (Sahna et al 2002b, 2005, Petrosillo et al 2009, Lamont et al 2011 have confirmed that the short-or long-term administration of melatonin at either physiological or pharmacological doses protected the heart against myocardial ischaemia/reperfusion damage. Furthermore, the beneficial effects of exogenous melatonin on the heart in physiological conditions such as ageing as well as in pathophysiological conditions, for example hyperthyroidism (Ghosh et al 2007), cadmium-induced oxidative damage (Mukherjee et al 2011) and myocardial hypertrophy (Reiter et al 2010c) have been demonstrated. However, the mechanism of the actions of melatonin is still complex and not yet fully explored.…”
Section: Cardiovascular Effects Of Melatoninmentioning
confidence: 99%
“…A realistic dose of Cd (5.1 mg/kg) was given to animals by oral gavage for 45 days (Mukherjee et al, 2011). After exposure of animals to Cd, they were made diabetic by i.p.…”
Section: Cadmium Chloride (Cdcl2)mentioning
confidence: 99%